Behavior of Ectatomma brunneum (Formicidae: Ectatomminae) preying on dipterans in field conditions - Gomes, Leonardo [UNESP]; Desuo, Ivan Cesar [UNESP]; Gomes, Guilherme [UNESP]; Giannotti, Edilberto [UNESP] (My University, 2009)
Behavioral traits of foraging activity in social insects require complex interactions between workers and the environmental conditions. The behavioral repertoire of foraging strategies depends on biotic factors, such as prey type, competition and natural enemies, and abiotic factors, such as temperature and humidity. The foraging activity and predation behavior of Ectatomma brunneum (Formicidae: Ectatomminae) onflies(Diptera:Calliphoridae and Muscidae) in field conditions were observed during 2006-2007. The foraging strategy was exclusively individual and the pattern of predation behavior involved detection/ localization, approachingandattackingacts.The majority of attacks were directed to the median part of the body (thorax) of the prey. The adults and larvae of Chrysomya albkepswere the most captured fly species. However, due to a complex interaction between biotic and abiotic factors and high behavioral flexibility more studies are needed to define patterns of foraging strategies for E. brunneum.
Keywords: Ants; Carrion; Flies; Foraging behavior; Forensic entomology; Social insects